1976
DOI: 10.1016/s0006-3495(76)85783-9
|View full text |Cite
|
Sign up to set email alerts
|

A method for measuring picosecond phenomena in photolabile species: the emission lifetime of bacteriorhodopsin

Abstract: We have measured the emission lifetime of bacteriorhodopsin at physiological temperatures to be 15 +/- 3 ps using a technique which employs a mode-locked dye laser, a sum frequency light gate, and a continuous flow system. We observe no concentration dependence of the lifetime over the range of 1.1 X 10(-4) M to 1.0 X 10(-5) M. We conclude that the emission which we observe comes from bacteriorhodopsin and not one of its photochemically produced intermediates, and that the emission cannot originate from the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

1978
1978
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 30 publications
(45 reference statements)
2
18
1
Order By: Relevance
“…These molecules (1 in 10,000 at room temperature, significantly higher as the temperature is lowered) are deflected by any "roughness" in the PDC surface and enter states near zero PDC that are not accessible to molecules in which protein deformation to P,, has taken place. Thus, the emitting state (or possibly even states), with a lifetime of 15 psec at physiological temperatures (30,31) or 40 psec at 77 K (29), is drawn to indicate zero PDC and, as is observed (31), has dynamic properties that are not correlated to the rate of production of the photochemical product at physiological temperatures or at 77 K. This is clearly understood in terms of our three-dimensional illustration in Fig. 2.…”
Section: Experimental Observationsmentioning
confidence: 74%
See 1 more Smart Citation
“…These molecules (1 in 10,000 at room temperature, significantly higher as the temperature is lowered) are deflected by any "roughness" in the PDC surface and enter states near zero PDC that are not accessible to molecules in which protein deformation to P,, has taken place. Thus, the emitting state (or possibly even states), with a lifetime of 15 psec at physiological temperatures (30,31) or 40 psec at 77 K (29), is drawn to indicate zero PDC and, as is observed (31), has dynamic properties that are not correlated to the rate of production of the photochemical product at physiological temperatures or at 77 K. This is clearly understood in terms of our three-dimensional illustration in Fig. 2.…”
Section: Experimental Observationsmentioning
confidence: 74%
“…However, the above experiments have not been able to demonstrate that this minimum can be populated from the batho intermediate. Furthermore, room temperature (30) and low temperature (77 K) (29) picosecond emission spectroscopy and picosecond absorption spectroscopy (25,31,32) have shown that the photochemistry occurs directly from the state produced by vertical excitation, whereas emission occurs by a parallel competing pathway from a state or states that are entered by molecules that do not proceed to the batho intermediate.…”
Section: Experimental Observationsmentioning
confidence: 99%
“…Considerable effort has been spent in the last years to elucidate the structure and the photochemistry of the purple membrane (for recent reviews, see Oesterhelt, 1976;Henderson, 1977). Most of the work so far has been devoted to the analysis of the photochemical reaction cycle of isolated purple membrane fragments in aqueous phase (Oesterhelt and Stoeekenius, 1973;Oesterhelt and Hess, 1973;Lewis et al, 1974;Dencher and Wilms, 1975;Kung et al, 1975;Lozier et al, 1975;Hirsch et al, 1976;Kaufmann et al, 1976;Lozier et al, 1976;Sherman et al, 1976;Becher and Ebrey, 1977;Goldschmidt et al, 1977;Marcus and Lewis, 1977;Renthal, 1977;Campion et al, 1977). While these studies have revealed the occurrence of a number of intermediate steps in the overall photocycle, the connection between the single photochemical reaction steps and the proton transfer process is not completely clear.…”
Section: Introductionmentioning
confidence: 99%
“…This method is particularly suited for laser pulses of moderate peak powers but very high repetition rate. Very low light level emissions with picosecond lifetimes were soon measured from bacteriorhodopsin (15 ± 3 ps) [13] and the Sz~So fluorescence ofxanthione (14±2 ps) [14]. Other early investigations using this technique include fluorescence measurements of rhodamine 6G [15], malachite green [16], cresyl violet, and HITC [17] as a function of the solvent viscosity.…”
Section: Historical Background Of the Time-gated Up-conversion Techniquementioning
confidence: 99%
“…Only a few examples will be given which emphasize the advantage of time-resolved fluorescence spectroscopy over time-resolved absorption spectroscopy due to the well-defined ground and excited states. In relation to the biochemical importance of retinyl chromophores in photoreceptor proteins (rhodopsin and bacteriorhodopsin [13]), the fluorescence decay of all-trans retinal in hexane consists of ultrafast (r = 30 fs), fast (r = 370 fs), and slow (r = 33.5 ps) components [69]. The photo active yellow protein from the purple bacterium Ectothiorhodospira halophila contains a thiol ester linked p-coumaric acid.…”
Section: Biological Systemsmentioning
confidence: 99%